Association between cancer surface area and histopathological parameters of laryngeal squamous cell carcinoma in total laryngectomy specimens - Tomanović, Nada; Tomić, Ana Marija; Mikić, Anton; Milovanović, Jovica; Djordjević, Vladimir; Trivić, Aleksandar (Vojnosanitetski pregled, 2022)
Background/Aim. Numerous histopathological parameters, such as cartilage penetration, perineural and lymphovascular invasion, presence of metastatic tissue in regional lymph nodes (LNs), extranodal extension (ENE) of nodal metastases, as well as the presence of cancer tissue on resection borders, are all important factors influencing survival in patients with laryngeal squamous cell carcinoma (LSCC). The aim of the study was to determine if there is an association between cancer surface area (CSA) and these histopathological characteristics. The presence of ENE of metastatic tissue in regional LNs was also investigated. Methods. In a retrospective study, one hundred and forty cases of LSCC were revised and processed after total laryngectomy. The cases were found in the archives of the Histopathology Laboratory of the Clinic for Otorhinolaryngology and Maxillofacial Surgery, University Clinical Center of Serbia. Results. A significant difference was found in CSA depending on cancer penetration into the thyroid cartilage, perineural invasion, and positive resection margins. Cancers with larger CSA were more common in the advanced T stage. Metastases were found in 36 out of 72 (50%) neck LN samples submitted for evaluation. The difference in CSA was also found depending on the presence of metastatic tissue in regional LNs. ENE was present in 69.4% of involved LNs, and it was more frequent in LNs 3 cm in size or larger. Conclusion. There is a significant difference in CSA depending on the presence of cartilage penetration, perineural invasion, presence of cancer tissue on resection borders, and presence of metastases in regional LNs. Larger cancers tend to be of a higher T stage. ENE is more common in LNs 3 cm in size or larger.